Labor Markets in Regional Trade Agreements: What Do We Know? - Jaime de Melo; Julie Regolo (Fondation pour les études et recherches sur le développement international (FERDI), 2013)
Globalization has failed to relax barriers to the movement of labor, especially unskilled workers. So have North-South Regional Trade Agreements (RTAs), while South-South RTAs have failed to implement good intentions. A literature review of the labor effects of RTAs underscores context specificity precluding generalizations across categories of RTAs. Most ex-ante studies have focused on global welfare effects rather than anticipated labor market effects while ex-post studies have had difficulty isolating any direct effects attributable to implementation of the RTA because of confounding effects as illustrated by a discussion of the wage puzzle in Mexico under NAFTA. The survey reviews labor market and wage results from ex-ante CGE estimates and ex-post household-based econometric estimates.
Keywords: F18; Q56; 330